2019
DOI: 10.1007/s10393-019-01460-0
|View full text |Cite
|
Sign up to set email alerts
|

Pig Exposure and Health Outcomes in Hospitalized Infectious Disease Patients in Vietnam

Abstract: Many infectious diseases have a zoonotic origin, and several have had major public health implications. Contact with animals is a known risk factor for zoonotic infections, although there are limited data on disease symptoms and pathogens associated with contact with different animal species. The rise in pig production in Southeast Asia has contributed to the emergence and re-emergence of zoonotic infections caused by contact with pigs and pig products. To compare the symptom and pathogen profiles of hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Informed written consent was obtained from patients (or their parents/legal guardians) included in the study. Diagnostic results from this study were previously described in a paper by Robertson et al ( 2020 ) who looked at the association between contact with pigs and the symptoms and aetiology amongst patients in VIZIONS (Robertson et al 2020 ).…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…Informed written consent was obtained from patients (or their parents/legal guardians) included in the study. Diagnostic results from this study were previously described in a paper by Robertson et al ( 2020 ) who looked at the association between contact with pigs and the symptoms and aetiology amongst patients in VIZIONS (Robertson et al 2020 ).…”
Section: Methodsmentioning
confidence: 67%
“…The consumption of raw pig blood is common in Vietnam with 35% of respondents in surveys conducted in Hanoi reporting consumption of the dish Tiet canh (raw blood pudding) in the previous year (Huong et al 2014 ). The risk of meningitis from S. suis from infected pigs is common, particularly in Asia (Mai et al 2008 ) and another analysis of the VIZIONS data found that over 26% of patients admitted with an enteric, respiratory or CNS infection had had contact with pigs, while eating/handling of raw meat, blood or viscera was the most common form of contact across all hospital sites (Robertson et al 2020 ). However, in our study, we only found an association between S. suis and slaughtering pigs.…”
Section: Discussionmentioning
confidence: 99%